Self-excited valve using a flat ring tube: Application to robotics - Nabae, Hiroyuki; Kitamura, Eigo (Frontiers in Robotics and AI, 2022)
Complex and bulky driving systems are among the main issues for soft robots driven by pneumatic actuators. Self-excited oscillation is a promising approach for dealing with this problem: oscillatory actuation is generated from non-oscillatory input. However, small varieties of self-excited pneumatic actuators currently limit their applications. We present a simple, self-excited pneumatic valve that uses a flat ring tube (FRT), a device originally developed as a self-excited pneumatic actuator. First, we explore the driving principle of the self-excited valve and investigate the effect of the flow rate and FRT length on its driving frequency. Then, a locomotive robot containing the valve is demonstrated. The prototype succeeded in walking at 5.2 mm/s when the oscillation frequency of the valve was 1.5 Hz, showing the applicability of the proposed valve to soft robotics.